Thermal and Magnetic Stability of van‐der Waals Antiferromagnet CrOCl from the Bulk to Monolayer Limit - Rounak Banerjee; Sai Uppala; Jan Kopaczek; Mohammed Y Sayyad; Patrick Hays; Renee Sailus; Seth Ariel Tongay (Advanced Materials Interfaces)
Abstract 2D magnetic materials have been at the forefront of quantum materials research owing to their attractive and exotic magnetic properties. However, most known examples of 2D magnets have low environmental and thermal stability, posing a significant challenge to their eventual device integration. This work reports on the thermal stability of a recently discovered environmentally stable transition metal oxyhalide, CrOCl. Using differential scanning calorimetry, thermogravimetric analysis, and temperature‐dependent X‐ray diffraction, the studies show that van der Waals (vdW) layers of CrOCl exhibit remarkable thermal stability, significantly surpassing the temperature requirements for CMOS technology. CrOCl undergoes a two‐step decomposition process, transforming into amorphous Cr2O3 at ≈620 °C by releasing chlorine from its surface. Additionally, thickness‐dependent thermal stability studies show no significant decrease in decomposition temperature, dropping from 630 °C in the bulk material to 550 °C in few‐layer samples and down to 500 °C in the monolayer. Further, comprehensive magnetization studies indicate that despite a reduction in overall magnetization, key magnetic properties such as saturation magnetization and spin‐flip behavior are retained even after extreme thermal stress. These findings offer the first insights into the thermal stability of these transition metal oxychlorides as potential candidates for robust magnetic devices requiring 2D vdW magnets.